Innovations in Developing Teacher Professional Competence - Yusupova Diloromxon Sabirdjanovna (International Journal on Integrated Education, 2021)
The state considers important aspects of achieving the quality and effectiveness of education in the conditions of New Uzbekistan. In terms of frequency, the professional competence of a teacher and its criteria, proposals and recommendations for the development of professional competence are described.